Acupressure intervention for children: A scoping review - Sri Ramdaniati; Mei Neni Sitaresmi; Fitri Haryanti; Arief Tarmansyah Iman (Belitung Nursing Journal)
Background: Acupressure is a popular form of complementary nursing among adults. It stimulates the body’s self-healing processes by enhancing energy flow, or “chi,” along meridian channels. Acupressure can address many health issues and is also used on children because it is painless and straightforward. Although acupressure has existed for centuries, research on its applications for children remains limited.